Hacking with kali practical penetration testing techniques - Broad, James (Syngress, 2014)
Hacking with Kali introduces you the most current distribution of the de facto standard tool for Linux pen testing. Starting with use of the Kali live CD and progressing through installation on hard drives, thumb drives and SD cards, author James Broad walks you through creating a custom version of the Kali live distribution. You'll learn how to configure networking components, storage devices and system services such as DHCP and web services. Once you're familiar with the basic components of the software, you'll learn how to use Kali through the phases of the penetration tests.